Infection of Primary Bovine Macrophages with Mycobacterium avium Subspecies paratuberculosis Suppresses Host Cell Apoptosis - Kabara, Edward; Coussens, Paul M. (Frontiers in Microbiology, 2012)
Mycobacterium avium subspecies paratuberculosis (MAP) is able to survive intracellularly in macrophages by preventing normal phagosome maturation processes utilized to destroy bacteria. Infected macrophages often undergo apoptotic cell death to efficiently present bacterial antigens to the host adaptive immune system in a process known as efferocytosis. Recent studies with Mycobacterium tuberculosis (MTB) showed that macrophages infected with MTB are less likely to undergo apoptosis than control, uninfected cells. It is proposed that regulation of macrophage apoptosis is an important immune evasion tactic for MTB. Based on the similarity of MAP and MTB, we hypothesized that MAP-infected macrophages would be resistant to apoptosis compared to uninfected cells within the same culture and to cells from uninfected cultures. Our results demonstrate that, indeed, populations of MAP-infected macrophages contain fewer apoptotic cells than similar populations of control cells, and that MAP infection reduces the sensitivity of infected macrophages to induction of apoptosis by H2O2. We further demonstrate that MAP-infected cells contain reduced caspase activity for caspases 3/7, 8, and 9. Reduced caspase activity in MAP-infected macrophages is also maintained after H2O2 induction. This reduction in caspase activity is accompanied by a pronounced reduction in transcription of caspase genes encoding caspases 3, 7, and 8, but not for caspase 9, when compared to control, uninfected cells. Furthermore, MAP infection drastically effects the expression of several host cell proteins important for regulation of apoptosis. Studies using mutant MAP strains demonstrate the importance of bacterial specific factors in the control of host macrophage apoptosis. Together these data demonstrate that MAP specific factors may prevent caspase activity and caspase gene transcription as well as apoptosis signaling protein expression, resulting in decreased spontaneous host cell apoptosis and decreased sensitivity to apoptosis inducing agents.